2011
DOI: 10.1038/nprot.2011.351
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric real-time multispectral optoacoustic tomography of biomarkers

Abstract: Multispectral optoacoustic tomography (MSOT) has recently been developed to enable visualization of optical contrast and tissue biomarkers, with resolution and speed representative of ultrasound. In the implementation described here, MSOT enables operation in real-time mode by capturing single cross-sectional images in <1 ms from living small animals (e.g., mice) and other tissues of similar dimensions. At the core of the method is illumination of the object using multiple wavelengths in order to resolve spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
241
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(252 citation statements)
references
References 40 publications
1
241
0
1
Order By: Relevance
“…In addition, multispectral illumination at several wavelengths combined with spectral unmixing can reveal specific chromophores and fluorescent proteins, distinguishing between oxy-and deoxyhemoglobin, a technique termed multispectral optoacoustic tomography (MSOT) [29,30]. The large penetration depths and the relatively high resolution of $100 mm (note that this resolution is one tenth of the transport mean free path, $1 mm) make this approach ideal for macroscopic imaging of small animals [31][32][33]. Higher resolution might be achieved with optoacoustic tomography, as seen in Figure 1B-D where Razansky et al [34] show how MSOT can be used to resolve fluorophores in the brain of an adult transgenic zebrafish in vivo with a scalable spatial resolution of a few tenths of microns.…”
Section: Optoacoustic Imagingmentioning
confidence: 99%
“…In addition, multispectral illumination at several wavelengths combined with spectral unmixing can reveal specific chromophores and fluorescent proteins, distinguishing between oxy-and deoxyhemoglobin, a technique termed multispectral optoacoustic tomography (MSOT) [29,30]. The large penetration depths and the relatively high resolution of $100 mm (note that this resolution is one tenth of the transport mean free path, $1 mm) make this approach ideal for macroscopic imaging of small animals [31][32][33]. Higher resolution might be achieved with optoacoustic tomography, as seen in Figure 1B-D where Razansky et al [34] show how MSOT can be used to resolve fluorophores in the brain of an adult transgenic zebrafish in vivo with a scalable spatial resolution of a few tenths of microns.…”
Section: Optoacoustic Imagingmentioning
confidence: 99%
“…Banerjee et al were able to recover maps of μ a from the initial pressure map and boundary pressure measurements [16]. Razansky and colleagues modify their FBP algorithm to include an analytic calculation of fluence distribution where μ a is approximated based on a calibration technique [17,18]. Bauer et al showed improved reconstruction using hybrid diffuse optical tomography and PAT in large phantoms [19].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the multispectral optoacoustic tomography (MSOT) technique has emerged as a powerful tool to resolve spectrally-distinct absorbers by exciting the tissue with short laser pulses at multiple optical wavelengths [3], [4], [5]. In the common implementation of whole-body small animal imaging, MSOT can deliver crosssectional images of a living mouse in real time by simultaneous collection of optoacoustic signals with a concave array of cylindrically focused transducers [6], [7]. Three-dimensional image data can be then achieved by sample translation along the elevation direction of the array.…”
Section: Introductionmentioning
confidence: 99%